1962
DOI: 10.1111/j.1365-2672.1962.tb01133.x
|View full text |Cite
|
Sign up to set email alerts
|

THE PHYSIOLOGICAL AND SEROLOGICAL PROPERTIES OF STREPTOCOCCUS BOVIS AND RELATED ORGANISMS ISOLATED FROM CATTLE AND SHEEP

Abstract: The physiological and serological properties of 153 strains of Streptococcus bovis isolated from cattle and sheep have been studied. With 12 specific antisera it was possible to type 75 of the isolates. Neither the fermentation of arabinose nor of raffinose was related to type specificity. The only strain fermenting mannitol was serologically distinct from all the other strains, and the type antigen was probably located on the cell wall whereas with the other 11 types it was capsular. The distribution of these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

1964
1964
1999
1999

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 21 publications
2
23
0
Order By: Relevance
“…Unlike Streptococcus bovis, strain s I 9, both antigens were components of the cell walls. Group B streptococci also contain two carbohydrate antigens: a type-specific capsular material and a group-specific cell-wall carbohydrate (Lancefield, The work reported here supports the view that Streptococcus bovis can be separated into distinct serological types (Medrek & Barnes, 1962). Eventually, with greater knowledge of the iminunochemistry of the carbohydrates associated with S. bovis, it seems feasible to assume that a useful system for the classification of these streptococci may be obtained, which will compare favourably with that employed for the haemolytic streptococci.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Unlike Streptococcus bovis, strain s I 9, both antigens were components of the cell walls. Group B streptococci also contain two carbohydrate antigens: a type-specific capsular material and a group-specific cell-wall carbohydrate (Lancefield, The work reported here supports the view that Streptococcus bovis can be separated into distinct serological types (Medrek & Barnes, 1962). Eventually, with greater knowledge of the iminunochemistry of the carbohydrates associated with S. bovis, it seems feasible to assume that a useful system for the classification of these streptococci may be obtained, which will compare favourably with that employed for the haemolytic streptococci.…”
Section: Discussionsupporting
confidence: 71%
“…Previous studies have shown that Streptococcus bovis can be separated into at least 12 serological types on the basis of type-specific carbohydrates (Medrek & Barnes, 1962). These type-specific reactions were considered, in most instances, to be due to a capsular material.…”
Section: Resultsmentioning
confidence: 99%
“…As noted by other workers (6, 17, 37), many Streptococcus bovis strains do not react with group D All of our Streptococcus bovis strains were of human origin, and our results should not be extrapolated to the Streptococcus bovis strains isolated from animals. Animal strains are biochemically somewhat different; many ferment arabinose but not mannitol, and glucan production correlates more with arabinose fermentation than with mannitol fermentation (11,29). It was these streptococci, not the mannitol fermenters, that Oria-Jensen called Streptococcus bovis (33,39; reviewed by Kiel and Skadhauge [22], who cited Friedberg [17]).…”
Section: Characteristics Of Streptococcus Salivariusmentioning
confidence: 99%
“…equinus. These broad divisions were also supported by serological evidence, as type antigens occurring in the strains within each subdivision are distinct from those found in strains within the other subdivisions (Skadhauge, 1950 Medrek & Barnes, 1962).…”
Section: Introductionmentioning
confidence: 80%